Prevalence of overweight preschool children in public day care centers: a cross-sectional study - Nascimento, Viviane Gabriela; Silva, Janaína Paula Costa da; Bertoli, Ciro João; Abreu, Luiz Carlos; Valenti, Vitor Engrácia; Leone, Claudio (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Brazil is undergoing a period of epidemiological transition associated with demographic and nutritional changes. The prevalence of obesity is also increasing in children and is causing numerous health problems that are becoming public health issues. The aim here was to evaluate the prevalence of overweight among children of two and three years of age. DESIGN AND SETTING: Cross-sectional study in municipal day care centers in Taubaté, state of São Paulo, Brazil. METHODS: Weight and height measurements were made on 447 preschool children forming a probabilistic randomized sample. Their body mass index (BMI) was calculated. Their nutritional status was classified using the World Health Organization reference cutoff points (2006). Their mean weight, height and BMI were compared according to their age and sex. RESULTS: The mean values for the final sample (n = 447) were as follows: mean age: 38.6 months (± 3.5) and Z scores for: weight/height (W/H): 0.50 (± 1.22); height/age: -0.03 (± 1.07); weight/age (W/A): 0.51 (± 1.23); and BMI: 0.51(± 1.23). The prevalence of overweight children (BMI > 1 z) was 28.86%, while the prevalence of underweight children (BMI < -2 z) was 0.89%. There were no differences in mean BMI among the two and three-year age groups (P = 0.66). CONCLUSION: A high prevalence of overweight was observed in the sample of two and three-year-old children, with practically no malnutrition, thus showing that a significant nutritional transition may already be occurring, even in medium-sized cities of developing countries.